2004
DOI: 10.1163/22941932-90000352
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Properties of Light Conducted in Stems of Woody Plants Show Marked Seasonal Differences Suggesting a Close Relationship With Photomorphogenesis

Abstract: Optical properties of stems in woody plants were investigated in the winter–spring period, and compared with those in the summer–autumn period. In both periods light could enter the interior of the stems and was conducted efficiently along the axial direction. Vessels, fibers and tracheids were all involved in this axial light conduction. However, spectral properties of the light conducted by stems differed in different periods. The light conducted in stems of the winter–spring period showed higher relative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Among these, the fibres and vessels die upon maturation. As indicated previously (Sun et al, 2003(Sun et al, , 2004, the light conducted by fibres and vessels is not restricted to the light conductors only, but in fact leaks out to the surrounding living tissues during axial conduction. This has been verified in recent investigations of the spectral properties of specific tissues and cells, and even specific parts of a tissue or cell, by means of a fine light-guide detector (Q Sun and H Suzuki, unpublished data).…”
Section: Functional Significance Of the Internal Light Environment Ofmentioning
confidence: 78%
See 2 more Smart Citations
“…Among these, the fibres and vessels die upon maturation. As indicated previously (Sun et al, 2003(Sun et al, , 2004, the light conducted by fibres and vessels is not restricted to the light conductors only, but in fact leaks out to the surrounding living tissues during axial conduction. This has been verified in recent investigations of the spectral properties of specific tissues and cells, and even specific parts of a tissue or cell, by means of a fine light-guide detector (Q Sun and H Suzuki, unpublished data).…”
Section: Functional Significance Of the Internal Light Environment Ofmentioning
confidence: 78%
“…These findings also identify certain differences between the structural components involved in light conduction in herbaceous and woody species. In woody species (Sun et al, 2003(Sun et al, , 2004, vascular tissue (consisting mainly of secondary xylem and secondary phloem) comprises the majority of the stem and root structure, and the vessels, fibres, and tracheids were the only efficient axial Fig. 6.…”
Section: Differences In Internal Stem and Root Light Conduction Betwementioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that the peaks and shoulders of transmittance were found in the ranges of 870-900 nm and 930-950 nm, and at around 1100 nm. Sun et al (2004) investigated longitudinal light-transmittances of shorter NIR (<950 nm) in the fresh wood of 6 conifer species (Ginkgo biloba, Metasequoia glyptostroboides, Abies firma, Cryptomeria japonica, Chamaecyparis obtusa and Pinus densiflora). They found three peaks in the wavelength ranges of 730-740 nm, 820-830 nm and 918-925 nm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Tsuchikawa and Tsutsumi (1996) indicated that light with a wavelength of 1100 nm had high transmittance in the wood of Picea sitchensis. The longitudinal light-transmitting properties of shorter NIR (<950 nm) have been investigated in the fresh branches and roots of some wood species (Sun et al 2003(Sun et al , 2004. However, there had been no comprehensive study investigating the transmittance of shorter NIR in wood, by species, using xylarium-authorized wood samples.…”
Section: Introductionmentioning
confidence: 99%